A SIMPLE MODEL OF AN ECONOMICAL PROBLEM IN THE MATHEMATICA ENVIRONMENT - FAJKUS, Martin (Trends in education, 2016)
The article deals with a simple problem from microeconomics. According to the given data and taking into account the character of the problem an appropriate mathematical model is created, the way how to solve it is shown and the result is properly interpreted. Further it is shown how the problem could be solved by the help of IT, especially the Mathematica environment. The use of computers in teaching is now very common in different subjects not only at technical universities. In the article the relationship between mathematical symbols, economical terms and real-life terminology is discussed.
Keywords: microeconomics; Mathematica; mathematical model; computers in teaching